Potential applications of conditional cash transfers for prevention of sexually transmitted infections and HIV in Sub-Saharan Africa - Medlin, Carol (Policy research working paper, 2008)
"A growing number of developing countries have introduced conditional cash transfer programs that provide money to poor families with certain contingencies attached - such as requiring school attendance or regular immunization and health check-ups. As the popularity of conditional cash transfer programs has grown, experimentation with potential applications in other areas of health, such as sexual and reproductive health, and HIV prevention, in particular, has also increased. Evaluations of conditional cash transfer programs have focused almost exclusively on uptake of health and educational services, which make relatively low demands of participants compared with more complex interventions, which require the cessation of risky behaviors, such as smoking, obesity, and substance abuse. The literature on contingency management - based on the principle that behavioral change occurs when appropriate behaviors are reinforced and rewarded - provides a richer picture of the complexity of the use of conditionality to encourage healthy behavioral change. This paper examines developing countries' experiences with conditional cash transfer programs and the results of trials in clinical settings on the efficacy of contingency management, and addresses their relevance for designing conditional cash transfer programs to address risky sexual behavior and promote the prevention of sexually transmitted infections and HIV in Sub-Saharan Africa. "--World Bank web site